Stoletniki med nami in mi z njimi / Centenarians among us and we with them - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
A hundred years. Is that plenty or a little? It depends on how we view it and on what and who we view. For a human it is a lot; for some institutions it is relatively little. But regardless of this, a hundred years is a hundred years. It is a type of a milestone that needs to be remembered for the sake of descendants and simultaneously the past needs to be closely examined. Without the past there is no future, is a saying whichis still true. Those who try to erase the past, erase a part of themselves. The past is us; it represents our ancestors. It is something that has given us the foundations on which we stand and from which we can develop. Without them, neither we nor the future would exist. This is why everything where we are at the moment is a continuation of the past, even though some believe that history began only with them.